Effect of extraction methods on yield, oxidative value, phytosterols and antioxidant content of cocoa butter - Mohamad, Roiaini; Seyed H. M.,; Selamat, Jinap; Hussain, Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Cocoa beans are rich in numbers of beneficial bioactive compounds such as phenolics and phytosterols, which benefits to human being. The suitable extraction method is needed to produce high quality and quantity of cocoa butter and other bioactive compounds. There are many extraction method to extract these compounds such as Soxhlet extraction, supercritical fluid extraction, ultrasound extraction method and others. The objective of this study is to determine the effectiveness of the different extraction methods producing high yields of cocoa butter, lower oxidative value, stable phytosterols and antioxidant content. The cocoa beans were subjected to different extraction methods such as Soxhlet extraction (SE), Ultrasonic extraction method (USE), Supercritical carbon dioxide (SCO2) and Supercritical carbon dioxide with co-solvent (SCO2-Ethanol). Cocoa butter extracted using SCO2-Ethanol has significantly (p<0.05) obtained highest cocoa butter yield (37.05%) and phytosterols content (6441 μg/g of extract) compared to SE (28.87% and 4960 μg/g of extract), SCO2 (31.32% and 5492 μg/g of extract) and USE (34.81% and 5106 μg/g of extract). Meanwhile, the oxidative value of SCO2-Ethanol was significantly (p<0.05) obtained lowest value compared to other extraction methods. Extraction method are crucial in cocoa industry to minimise the cost during processing, obtain maximum extraction yield and preserve the bioactive compounds thus will improve the value of cocoa butter improve the value of cocoa butter.